1998
DOI: 10.1128/aem.64.12.4965-4972.1998
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofcryGenes in a MexicanBacillus thuringiensisStrain Collection

Abstract: Mexico is located in a transition zone between the Nearctic and Neotropical biogeographical regions and contains a rich and unique biodiversity. A total of 496 Bacillus thuringiensis strains were isolated from 503 soil samples collected from the five macroregions of the country. The characterization of the strain collection provided useful information on the ecological patterns of distribution of B. thuringiensis and opportunities for the selection of strains to develop novel bioinsecticidal products. The anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
149
3
35

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(204 citation statements)
references
References 26 publications
17
149
3
35
Order By: Relevance
“…This observation is consistent with the physical location of cry1I genes, which have been reported to be in close vicinity to other genes of the cry1 subfamily [13,27,52,53]. Another frequent combination found almost world-wide is the linkage cry1C^cry1D [15,17,18,51,54]. In fact, only Kim et al [30] reported the common presence of cry1C alone.…”
Section: Relative Frequency Of Cry Genessupporting
confidence: 79%
See 2 more Smart Citations
“…This observation is consistent with the physical location of cry1I genes, which have been reported to be in close vicinity to other genes of the cry1 subfamily [13,27,52,53]. Another frequent combination found almost world-wide is the linkage cry1C^cry1D [15,17,18,51,54]. In fact, only Kim et al [30] reported the common presence of cry1C alone.…”
Section: Relative Frequency Of Cry Genessupporting
confidence: 79%
“…The DNA used as template is obtained either by the typical lysis extraction and puri¢cation methods [14,18,29], or by simple time-saving lysis of a cell suspension using physical methods. In the latter case, DNA is usually released by boiling the suspension for 2^10 min [13,15,30], or by alternate freezing (370 ‡C) and boiling steps [17,24,26]. Template is added to the reaction mixture (¢nal volume 50^100 Wl) and the three-step ampli¢cation cycles are performed 25^35 times.…”
Section: Identi¢cation Of N-endotoxins By Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The 445 isolates of B. thuringiensis were grown for 12 h at 30°C in Petri dishes with GEN nutrient medium (5 g yeast extract, 8AE8 g glucose, 10 g NaCl, 20 g agar in 1000 ml distilled water). A loop of each isolate was transferred to 100 ll sterile distilled water, the mixture was homogenized and stored at )20°C for 3 h, then immediately placed in a water bath at 100°C for 10 min to lyse the cells and finally centrifuged for 10 s at 9280 g. This supernatant was used for PCR as DNA template (Carozzi et al 1991;Ceró n et al 1994Ceró n et al , 1995Bravo et al 1998). General primers were used to characterize cry gene content (cry1, cry2, cry4 and cry11).…”
Section: Determination Of Cry Genesmentioning
confidence: 99%
“…These strains have been isolated from diverse microhabitats such as soil, plant leaves, dead insects and stored grain, as well as aquatic environments such as marine sediments, mangroves and fresh water. Characterization of these collections has revealed the great variability and diversity of B. thuringiensis in nature (Ben-Dov et al 1997;Bravo et al 1998;Ben-Dov et al 1999;Ichimatsu et al 2000;Iriarte et al 2000;Kim 2000;Maeda et al 2001;Mizuki et al 2001;Arango et al 2002;Maduell et al 2002;Uribe et al 2003).…”
Section: Introductionmentioning
confidence: 99%